Aprendizagens da lei 11.645/08 na experiência intercultural dos XII Jogos dos Povos Indígenas em Cuiabá-MT - Eichholz, Gerda Langmantel (2015)
This dissertation discusses the learning on Law 11.645/08 and the cultural experience that took place during the XII Indigenous People Games (XII JPI in Portuguese) in Cuiabá- MT, based on teachers' formation on intercultural education perspective, which aimed to prepare teachers and students from public schools at the municipality, to the meeting with the Other, the indigenous. The objective of the research was to understand how the relationships between teachers' knowledges and practices were established, and the knowledges and practices that, in an intelectual perspective, is made clear from students, who can qualify the pedagogical practice on the perspective of inclusion of histories and cultures of indigenous people in the school. To do so, the researcher has participated since the elaboration and execution process of the formation course, the follow-up to the teachers' pedagogical projects who participate in the course offered by UFMT, to the organization and follow-up of students with their teachers, to the Indigenous People Games. Investigation was based on action research on a qualitative approach, which used as instruments: a questionnaire, field notes and filming. On this qualitative research, the conflicts between the colonialist and postcolonialist conception show up, bringing the conflicts as a migrant in indigenous land, as well as a teacher who faces the prejudice to the indigenous people in the city schools. The research dynamics, and the researcher's, merge and lead to the deepening of the referentils that base the ethnical-ratial and ethnical-cultural conflicts in Mato Grosso, whose land conflict happens due to the greed of agrobusiness and the permanent colonisation with the defense of native people's rights to remain on their ancestors' traditional territories, which the new generations depend on, to perpetuate their colective lifestyle and in balance with the environment that feeds them in all dimensions of life. The colonizer's life is registered on historiographical production, as well as didactic and paradidactic publications driven to children and that contribute to deny the multiethnical, pluricultural character of Brazilian population. The passing of Law 11.645/08 is necessary, however, facing the hegemonic culture that takes place against the recognition and diversity respect processes, the Law hasn't been applied in Cuiabá schools yet. Data obtained on formation and pedagogical intervention process were qualitatively analysed and described in an interpretative, reflexive proposition of pedagogical praxis, considering that a pedagogical and curricular conception that respects and values cultural diversity demands to look at the school in a diferent way, i.e., to look at it as a cultural, social space, where several ways to relate, to communicate and to act and to think. Students' and teachers' discourse were articulated to the theoretic fundaments of culture, alterity, cultural diversity, identity, interculturality and corporeity, with the goal to understand the deconstruction process of stereotypes and prejudices built and perpetuated in people's imagination, regarding indigenous people. With the research, the discussion on Law 11.645/08 deepen, spreading reflexive ideas on initial, continued formation, and teacher formation, in order to humanize the social relationships which permeate the school environment, which aims to educate for companionship on diversity, ruled on knowledge encourage on the respect to the indigenous people.